APPLICATION OF THE CONCEPT OF AGRICULTURAL PERMACULTURE WITH ISLAMIC SOCIAL ECOLOGICAL APPROACH IN BUILDING A TOURISM VILLAGE IN HUTA BARU SIL VILLAGE - Jamaluddin Siregar; Zuhrinal M. Nawai (Jurnal Ekonomi, 2022)
The people of Huta Baru Sil Village who do farming as their main livelihood are Rubber, Oil Palm and Horticulture Farmers. Everyone seeks to make maximum use of the land to produce food that will improve the quality of his life. The plants include rice, chilies, long beans, cucumbers, kale, spinach, sugarcane juice, sweet potatoes, corn, pumpkin, onions, and others. For livestock in Huta Baru Sil Village, namely poultry such as ducks, chickens and goats. The purpose of this research is to show how permaculture principles can be adapted to the culture of the local community and how effective design principles can prevent the spread of social inequality, supported by verses of the Qur'an. This research method uses a qualitative method with a descriptive research type, namely by elaborating the qualities and conditions found in the case study locations. The results of this study indicate that the existence of the Permaculture Agricultural Concept with an Islamic Socio-Ecological Approach in the Development of Tourism Villages in Huta Baru Sil Village can have a reciprocal effect between Huta Baru Sil Village and neighboring villages, so that there is a connected relationship and within this linkage there are resources countless resources flowed to improve the Village economy and strengthen the relationship between Huta Baru Sil Village and other Villages. With the concept of Permaculture Agriculture with an Islamic Socio-Ecology approach, this can be a foundation in carrying out Islamic-based social movements originating from the Al-Qur'an and Hadith in environmental destruction activities that focus on Permaculture Agriculture, especially those in Indonesia.